A Brief Introduction of Indonesian Culture and Its National Identity to College Students in the University of Nueva Caceres: Pengenalan Singkat Budaya Indonesia dan Identitas Nasionalnya kepada Mahasiswa Universitas Nueva Caceres - A. Amrizal; Zohri Hamdani (Yayasan Ahmar Cendekia Indonesia, 2022)
Culture is the identity of a nation. The cultural diversity of the archipelago will further strengthen the identity of the Indonesian nation. The purpose of this service is to introduce Indonesian culture and its national identity to English-language education students at the University of Nueva Caceres, Naga City, Philippines. This Community service activities are carried out for English language education students at the University of Nueva Caceres, Naga City, Philippines. In this activity, data is gathered through observations, interviews, and studies of the literature. There are three steps to this activity: planning, implementation, and evaluating. The result showed that both English education lecturer and students at the University of Nueva Caceres in Naga City, Philippines, learnt more about Indonesian culture and national identity, and they also acquired more vocabulary in the Indonesian language. This means that the activity had a good effect. Abstrak Kebudayaan merupakan identitas suatu bangsa. Keanekaragaman budaya nusantara akan semakin memperkuat jati diri bangsa Indonesia. Tujuan pengabdian ini adalah untuk memperkenalkan budaya indonesia dan identitas nasionalnya kepada mahasiswa pendidikan bahasa inggris the University of Nueva Caceres , Naga City, Philippines. Kegiatan Pengabdian masyarakat dilakukan pada mahasiswa pendidikan bahasa inggris the University of Nueva Caceres , Naga City, Philippines. Pengumpul data dalam kegiatan ini menggunakan observasi,interview and studi literature. Tahapan dalam kegiatan ini ada tiga yaitu perencanaan , pelaksanaan dan evaluasi. Hasil dari kegiatan adalah bahwa baik dosen maupun mahasiswa pendidikan bahasa inggris the University of Nueva Caceres , Naga City, Philippines, ada mengalami penambahan wawasan dan pengetahuan mengenai budaya indonesia dan identitas nasionalnya serta menambah kosakata dalam bahasa indonesia artinya kegiatan ini memberikan dampak yang positif .